OUTCOMES OF LAPAROSCOPIC CHOLECYSTECTOMY IN DIFFERENT GRADES OF GALL BLADDER INFLAMMATION A TERTIARY CARE CENTRE EXPERIENCE - Ali, Amir; Syed, Mukarram Hussain; Khan, Taimoor Ashraf; Aslam, Farheen; Ahmad, Gufran; Akbar, Afnan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find the outcomes of laparoscopic cholecystectomy in gall bladders with all grades peri-operative inflammation.Study Design: Prospective observational study.Place and Duration of Study: Combined Military Hospital, Rawalpindi, from Nov 2018 to Aug 2019.Methodology: All patients with symptomatic gall bladder disease who underwent laparoscopic cholecystectomy (emergency/elective procedure) and American Anesthesiology Society (ASA) Score 1 or 2 were included in the study.Results: A total of 330 patients with a mean ± SD age of 48.01 ± 14.13 years underwent laparoscopic cholecystectomy. Out of 330 patients, 129 (39.1%) had acute inflammation of gall bladder while 201 (69.9%) cases were operated electively. The rate of conversion and complications were somehow lesser in both categories as the overall conversion rate was 15 (4.5%).Conclusion: Laparoscopic cholecystectomy is the gold standard treatment for symptomatic gall stones. Moreover, it is safe option in acute and chronic inflammation of Gall bladder if performed by a experienced laparoscopic surgeon.